Characters on a wall [compact disc] - Sclavis, Louis (ECM Records, 2019)
Louis Sclavis's thirteenth ECM recording finds the French clarinetist drawing inspiration from two sources, the street art of Ernest Pignon-Ernest, and the interpretive originality of a splendid new quartet. In the Sclavis group, gifted bassist Murcia and expressive drummer Lavergne join pianist and key collaborator Moussay making this the first time Sclavis has explored, in a characteristically individual fashion, the classic jazz format of reeds, piano, bass and drums on an ECM disc.